The effects of sediment loading on morphology and flood risk in a lowland river system - Dangerfield, Stephen F. (2013)
Diffuse sources of sediment may have important implications for flood risk management (FRM), especially as catchment sediment yields are predicted to increase in future. UK legislation requires FRM to work with natural processes wherever possible, including accounting for sediments. However, the importance of wash-material load to FRM has been under researched and both a robust evidence-base and practical sediment models are needed to identify, prioritise and justify sediment-related catchment management.